Efektivitas Promosi Wisata Berbasis Website Menggunakan Analisis SWOT di Tanjung Duriat - Salsabila Fatin Adilah; Oman Sukirman; Dally Nur Arif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of information technology, especially the internet, has significantly changed the way tourism is promoted. Websites as digital media play an important role in promotional strategies, especially for tourist destinations that want to expand their reach and increase tourist visits. This research aims to analyze Tanjung Duriat's tourism promotion strategy through the website with a SWOT analysis approach, to identify the destination’s strengths, weaknesses, opportunities, and threats faced by the destination. The research method used is a qualitative method with a descriptive approach. Data were obtained through interviews, direct observation of the website, and study of related literature. The results showed that the Tanjung Duriat website has great potential to promote the tourist destination. However, there are still some weaknesses such as the lack of content updates and website features. In addition, the website promotion strategy also faces challenges in significantly increasing visibility and number of visits. Based on the SWOT analysis, this study suggests improving the quality of website content and features, as well as optimizing the use of social media connected to the website to increase tourist attraction. The website-based Tanjung Duriat tourism promotion strategy using the W-O strategy, strategy was chosen because the Tanjung Duriat website does not yet have a person specifically to manage the website. In the W-O strategy, there is a strategy to add human resources specifically to manage the website, if there is someone who is devoted to managing the website, it will make it easier for Tanjung Duriat to optimize the website which is used as one of the tourism promotion media. With the right strategy, the Tanjung Duriat website is expected to be an effective promotional tool in increasing tourist visits to these destinations.